2023
DOI: 10.4314/jae.v27i2.5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Digitalization of Agriculture in Nigeria

Abstract: It has become difficult to articulate the impacts, needs and challenges of digitalization of agriculture due to the extensive nature of publications relating  to the digitalization of the agricultural sector. This review evaluated the effect of digitalization of agriculture on improved food production and standard of  living, identified the training needs of extension staff and clientele for digitalization of agriculture, and highlighted the challenges of digitalization of  agriculture. From an initial search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Izuogu et al [ 29 ] used two terms to explain the concept of digital agriculture: digitization and digitalization. Digitization is the non-theoretical change of analog information into digital messages.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Izuogu et al [ 29 ] used two terms to explain the concept of digital agriculture: digitization and digitalization. Digitization is the non-theoretical change of analog information into digital messages.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Digital technology development in the agri-food value chain has multidisciplinary dimensions [ 4 ]. It affords all the stakeholders in agriculture to be part of beneficial changes; it reduces the role of middlemen, expands market opportunities, improves the links between extension and research centers, and makes the agricultural system and productivity highly efficient [ 4 , 29 , 40 ]. The incorporation of digital farming into agricultural development enhances industrial integration and innovation, and supports the revitalization of rural areas [ [41] , [42] , [43] , [44] ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to a recent review by Izuogu et al. (2023) , the digitalization of agriculture in Nigeria has reduced middlemen’s participation in agriculture, offered small-holder farmers opportunities to improve their productivity and markets, and strengthened the connections between extension and research facilities.…”
Section: Overview Of the Status Of Field Phenotyping In Africamentioning
confidence: 99%
“…According to a recent review by Izuogu et al (2023), the digitalization of agriculture in Nigeria has reduced middlemen's participation in agriculture, offered small-holder farmers opportunities to improve their productivity and markets, and strengthened the connections between extension and research facilities. The authors demonstrated that for effective digitalization of agriculture, training was required in the areas of skills development, use of demand-driven digital services, digital privacy, and security issues.…”
Section: The Case In Nigeriamentioning
confidence: 99%
“…Also, it introduced the SeedCodex and Seed Tracking tools to check the activities of fraudsters in the seed value chain. While the Seed-Codex involves the digital coding of certified seeds which becomes visible when scratched, the Seed Tracker monitors the certified seeds from production to harvesting (Mabaya et al, 2021;Izuogu et al, 2022).…”
Section: Seed Qualitymentioning
confidence: 99%